Aplikasi Metode Abajadun dan Tahsinul Kitabah dalam Pembelajaran Kaligrafi Arab : Studi Kasus di Sekolah Kaligrafi Al-Qur’an PP. Mambaul Maarif Denanyar Jombang - Anas, Muhammad Choirul (Indonesian Proceedings and Annual Conference of Islamic Education (IPACIE), 2022)
Currently, along with the role of IT (Information Technology), which is very fast in making handwriting slowly decline, which is alarming, especially Arabic calligraphy, students starting from the elementary level even many students complain about the bad and unreadable of their Arabic writing, as well as a student. Teachers find it difficult to read the answers from the test results and their students' homework, thus harming student achievement, answering exam questions with poor handwriting so that the proofreaders cannot read them, which can reduce the value even though the answer is correct. This research is field research with a qualitative descriptive method. Data collection techniques using observation, interview, and documentation methods. Test the validity of the data using data triangulation. Data were analyzed using the Miles and Huberman technique by reducing data, presenting data, verifying, and concluding. The study results: (1) Abajadun and Tahsinul kitabah methods are learning tools that are applied so that students can write Arabic calligraphy properly and correctly. (2) The learning process: analyzes internal abilities, makes strategic plans, and assessments are based on student learning outcomes. (3) Supporting factors include quality teacher guidance, systematic learning, student and teacher manuals, and additional hours of online correction outside the classroom. The inhibiting factors are an unsupportive environment outside the classroom, varying learning distances, and students who incidentally have responsibilities at home and on campus.